1994
DOI: 10.1152/jappl.1994.76.5.1882
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial pressure and ANP release during prolonged exercise in a hot environment

Abstract: To investigate the relationship between right atrial pressure (RAP) and atrial natriuretic peptide (ANP) release during prolonged exercise in a hot environment (30 degrees C, 20% relative humidity), we studied with a Swan-Ganz catheter five male volunteers exercising on a cycle ergometer at 60% of peak aerobic power for 50 min. The ANP level increased from 14 +/- 3 (SE) to 69 +/- 10 pg/ml (P < 0.001) during the first 10 min of exercise as RAP rose from 4.3 +/- 0.8 to 6.9 +/- 1.1 mmHg (P < 0.001). The 10-min AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
0
19
2
Order By: Relevance
“…In man, head-out immersion (Ogihara et al 1986, Epstein et al 1987, Leung et al 1987, Warner et al 1991, Nakamitsu et al 1994, or headdown tilt (Allen et al 1989, Arjamaa et al 1992 are among the factors that elevate plasma ANP. Nose et al (1994), measuring the right atrial pressure with an intraluminal catheter, showed a correlation between plasma ANP and right atrial pressure during prolonged exercise in man.…”
mentioning
confidence: 94%
“…In man, head-out immersion (Ogihara et al 1986, Epstein et al 1987, Leung et al 1987, Warner et al 1991, Nakamitsu et al 1994, or headdown tilt (Allen et al 1989, Arjamaa et al 1992 are among the factors that elevate plasma ANP. Nose et al (1994), measuring the right atrial pressure with an intraluminal catheter, showed a correlation between plasma ANP and right atrial pressure during prolonged exercise in man.…”
mentioning
confidence: 94%
“…Atrial natriuretic peptide (ANP) is an important volume-regulating hormone that is released by cardiac muscle cells in response to elevations in right atrial pressure [1][2][3][4]. Under conditions of volume expansion, circulating ANP reduces the central blood volume through its natriuretic and diuretic actions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of volume expansion, circulating ANP reduces the central blood volume through its natriuretic and diuretic actions [5]. Prolonged exercise in the heat also stimulates plasma ANP release, initially via atrial distension and then by progressive increases in heart rate associated with rising body temperatures and plasma catecholamine levels [2,6]. Under these conditions, higher circulating ANP concentrations are associated with larger blood volume reductions caused by sweat-induced dehydration [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANP is released by distension, primarily from atrial tissue in healthy subjects (Nose et al, 1994). It has been proved that plasma ANP levels acted as a regulatory factor in the development of hypertension (Levin et al, 1998).…”
Section: Introductionmentioning
confidence: 99%